Anesthetic management of patients undergoing mediastinal mass operation - Tan, Jie-chao; Lin, Pei-shuang; He, Li-xian; Lin, Yong; Yao, Yun-tai; , the Evidence in Cardiovascular Anesthesia(EICA) Group (Frontiers in Surgery, 2022)
Objective: To summarize the anesthetic management of patients undergoing mediastinal mass operation. Methods: Electronic databases were searched to identify all case reports of patients undergoing mediastinal mass operation. Information such as clinical characteristics, perioperative management and patients’ outcomes were abstracted and analyzed. Results: Seventy-seven case reports with 85 patients aging from 34 days to 81 years were included. Mediastinal masses were located in anterior (n=48), superior (n=15), middle (n=9) and posterior (n=9) mediastinum, respectively. Clinical manifestations included dyspnea (n=45), cough (n=29), chest or radiating pain (n=12), swelling (n=8), fever (n=7) and chest distress (n=4). Most patients (n=75) had signs of compression or invasion of vital structures. General anesthesia (n=76) was the most commonly used method of anesthesia. Muscle relaxants were administered in 35 patients during anesthesia induction and spontaneous respiration was maintained in 37 patients. Mediastinal mass syndrome (MMS) occurred in 39 cases. Extracorporeal circulation was utilized in 20 patients intraoperatively. Three patients experienced cardiac arrest after ventilation failure and two patients died intraoperatively and one postoperatively. Conclusions: Peri-operative management of patients undergoing mediastinal mass operation could be challenging. Pre-operative multi-disciplinary discussion, well-planned anesthetic management and pre-determined protocols for emergency situations are all vital to patient safety.